Mechanisms of Ethanol-Induced Cerebellar Ataxia: Underpinnings of Neuronal Death in the Cerebellum - Hiroshi Mitoma (International Journal of Environmental Research and Public Health, 2021)
Ethanol consumption remains a major concern at a world scale in terms of transient or irreversible neurological consequences, with motor, cognitive, or social consequences. Cerebellum is particularly vulnerable to ethanol, both during development and at the adult stage. In adults, chronic alcoholism elicits, in particular, cerebellar vermis atrophy, the anterior lobe of the cerebellum being highly vulnerable. Alcohol-dependent patients develop gait ataxia and lower limb postural tremor. Prenatal exposure to ethanol causes fetal alcohol spectrum disorder (FASD), characterized by permanent congenital disabilities in both motor and cognitive domains, including deficits in general intelligence, attention, executive function, language, memory, visual perception, and communication/social skills. Children with FASD show volume deficits in the anterior lobules related to sensorimotor functions (Lobules I, II, IV, V, and VI), and lobules related to cognitive functions (Crus II and Lobule VIIB). Various mechanisms underlie ethanol-induced cell death, with oxidative stress and endoplasmic reticulum (ER) stress being the main pro-apoptotic mechanisms in alcohol abuse and FASD. Oxidative and ER stresses are induced by thiamine deficiency, especially in alcohol abuse, and are exacerbated by neuroinflammation, particularly in fetal ethanol exposure. Furthermore, exposure to ethanol during the prenatal period interferes with neurotransmission, neurotrophic factors and retinoic acid-mediated signaling, and reduces the number of microglia, which diminishes expected cerebellar development. We highlight the spectrum of cerebellar damage induced by ethanol, emphasizing physiological-based clinical profiles and biological mechanisms leading to cell death and disorganized development.